Social development and social transformation in Mongolia / Battsetseg Altangerel - Battsetseg, Altangerel (Research Management Institute (RMI), 2014)
Despite the vast data of social quality research about Asian societies, not many studies have been carried out on the current situation of social quality in Mongolia. The purpose of this paper is to highlight the level of social quality in Mongolia focusing on the dimensions of social inclusion and exclusion. Using the data of Mongolia's current society in terms of population growth; quality and access to social and welfare; social inclusion and services exclusion, this paper describes the situation of social change as a consequence of social transformation. The study refers to the social quality theory as the measurement of social progress, which should have certain useful implication for our assessment of the development process in Mongolia. Subsequently, this work increases the awareness and understanding of Mongolia's current social quality and provides a number of policy options and recommendations for improving social quality conditions in Mongolia.